Development and validation of liquid chromatography mass spectrometry (L/C/MS/MS) assay for the determination of plasma 4betahydroxycholestrol and cholesterol in HIV infected children in Africa - Ngwalero, Precious (Division of Clinical Pharmacology, 2016)
Includes bibliographical references